CONCERNING EDUCATIONAL PRAXEOLOGY - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2010)
This article is focusing on the problems of praxeology. The presented concept analysis, a short historic overview of its development show the gradually growing importance of praxis for educational sciences. It is not yet the integral part of educational sciences. The article reveals the multi faceted aspects of practical activities and their growing role for the development of schools and other educational institutions. The discussed possibilities and different types of educational praxeology show that the role of practice is very important for student as well as for for learner regardless of age. It increases the personal experience and learning, promotes the in-service training and specialist learning and professional improvement and consequently leads to the improvement of the quality of working life.Thus it is necessary for the educational science to get deep in the praxeology. The praxeology should be implemented in the whole system of the educational science, giving the priority to practice and practical skills development in education. However, the role of knowledge is important in the process of education, and knowledge should be used not only for thinking, but for the practice development as well.
Keywords: educational praxeology; contemplation; defect; interpretation; correction; talk; work; rapport